2011
DOI: 10.1002/ijc.26398
|View full text |Cite
|
Sign up to set email alerts
|

CDH1‐related hereditary diffuse gastric cancer syndrome: Clinical variations and implications for counseling

Abstract: CDH1 mutation carriers have a strongly increased risk of developing gastric cancer (GC) and lobular breast cancer (LBC). Clinical data of GC cases and surgical and histological data of prophylactic gastrectomies and mastectomies of all 10 Dutch CDH1 mutation families were collected. In vitro functional assays were performed to analyze the nature of the newly found missense mutation c.1748T>G (p.Leu583Arg). Ten different CDH1 mutations were found. Functional assays gave strong arguments for the pathogenic na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 117 publications
(100 citation statements)
references
References 40 publications
3
91
0
Order By: Relevance
“…1 A French team had previously reported similar observations in five carriers from two families. 2 We describe herein the case of a young patient with a history of CL, CP, and HDGC who turned out to carry a germline mutation in CDH1.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…1 A French team had previously reported similar observations in five carriers from two families. 2 We describe herein the case of a young patient with a history of CL, CP, and HDGC who turned out to carry a germline mutation in CDH1.…”
supporting
confidence: 57%
“…Indeed, CL/CP is rare in the general population with a reported frequency of 1-2/1000, whereas 4/58 (7%) mutations carriers in the Dutch study had CL/CP. 1,4 In France, where there are about 100 registered mutation carriers (French Cancer Genetics Network), six carriers (6%) including this one have CL/CP. 2 Second, we expect CL/CP to be very much underreported in CDH1 families, as current guidelines do not require cancer geneticists to enquire about CL/ CP among index cases and their relatives.…”
mentioning
confidence: 99%
“…14 Using functional in vitro assays, we demonstrated that cells expressing pathogenic CDH1 missense mutations fail to aggregate and become more invasive, in comparison with cells expressing wild-type (WT) E-cadherin, 5,12,[15][16][17][18][19][20][21][22] supporting their pathogenic relevance.…”
Section: Introductionmentioning
confidence: 86%
“…This measure, which is relatively easy to perform, is recommended here in addition to the IGCLC guidelines [12], because any residual gastric mucosa may be at risk for present or subsequent (pre)malignant lesions and inspection of the z-line may not in all cases be sufficient to achieve proximal clearance. In our Dutch experience of prophylactic gastrectomies in 29 CDH1 mutation carriers [17], we observed that three patients had to undergo re-intervention because of incomplete removal of proximal gastric mucosa. Moreover, the presence or absence of signet ring cells and/or residual gastric mucosa in the resection margins was not systematically documented.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…In HDGC caused by germline mutations in CDH1, the lifetime risk of developing gastric cancer is supposed to be higher than 80% and the mean age at diagnosis of gastric cancer is as young as 40 years of age, with a range from younger than 20 to older than 70. This large variation in age at diagnosis is seen even within families [17]. Female carriers have an additional high risk of developing lobular breast cancer (LBC) with a lifetime risk of 60% by the age of 80 years, rising from age 40 [12].…”
Section: Environmental and Inherited Factorsmentioning
confidence: 99%